Effect of the addition of psyllium (plantago ovata forsk) on the physicochemical characteristics of frozen banana pulp during storage (Research, Society and Development, 2021)
Psyllium is a soluble fiber that has aroused the interest of several researchers for presenting proven functional benefits such as reducing LDL cholesterol, controlling blood glucose, delaying gastric emptying time among others. This study aimed to elaborate a banana pulp added psyllium and verify the effect on the physicochemical parameters (pH, total titratable acidity, color and rheology) during 90 days of storage under different temperatures (- 8 °C and – 18 °C). The results showed that the addition of 3% psyllium altered some parameters: the pH did not present a significant difference at time 0, but at times 30 and 60 it showed a difference and at the end of storage it did not show any difference, the ATT did not change at time 0 , but from time 30 it showed a significant decrease until the end of the storage period, the psyllium having a darker color than the banana reduced the luminosity (L *), it was verified that the addition of psyllium increased the apparent viscosity of the pulp. Psyllium has the potential to be used in banana pulp, since the changes in pH and TTA did not affect the quality of the product and meet the recommended by the current quality and identity standard for banana pulp, being a viable product with functional properties that can receive health claims.